EVALUATION OF THE INFLUENCE OF DAMAGE ON THE PERMEATION AND DIFFUSION OF POLYMERIC GEOMEMBRANES - Mello, J. B. [UNESP]; Lavoie, F. L.; Lodi, P. C. [UNESP] (Centro Federal Educacao Tecnologica Rio Grande Norte, 2021)
Geomembranes have been used in order to waterproof and protect the soil, as well as groundwater and water sources. However, during the installation process they can become susceptible to the occurrence of mechanical damage (holes, micro-holes and / or tears). In this way, the permeability/permeation parameters can be affected and, in the event of leaks, leaks or small imperfections that increase the flow through the geomembrane, the entire work will have lost its function leading to the failure of the project. In this context, it is essential to study the permeation and the diffusive process in polymeric geomembranes, allowing to guarantee that their properties are within the parameters for which it was designed. Thus, this research evaluated the permeation and diffusion properties of high-density polyethylene (HDPE) and polyvinyl chloride (PVC) geomembranes in thicknesses of 1.0 mm when in contact with water and hydrocarbons. Intact and induced damage geomembranes (micro-holes, holes and abrasion processes) were evaluated. Permeation tests were performed according to the recommendations of ASTM E96. The diffusion test was performed with equipment developed and with the aid of gas chromatography. For this purpose, two types of local soils (sandy and clayey) were evaluated. The main results show that the damage caused to the geomembranes significantly influenced the permeation values. Gas chromatography proved to be extremely effective in detecting BTEX-type compounds.
Keywords: Geomembrane; permeation; BTEX; gas chromatography